The Composition, Abundance, and Biodiversity of the Insect Family of the Hymenoptera Order on Swampy Wetlands (SW) and Land Conversion (LC) in Palembang City - Riyanto Riyanto (Jurnal Biologi Tropis, 2020)
Urban development and population growth in the Palembang city, lowland swamps have been converted into swamps (SW) and land conversion (LC). Changes in habitat certainly have an impact on the composition, abundance, and diversity of the insect family of the Hymenoptera order. The purpose of writing this article is to inform the composition, abundance, and diversity of insect families of the Hymenoptera order in the SW and LC lands of Palembang city. This study used a survey method by exploring each research location four times. Determination of the research location using purposive sampling method with the reason to get different habitat conditions. The collection of insects is carried out in two ways, namely trapping and hands collecting. The results showed that 18 families of the Hymenoptera order, namely 4 to 7 families were found in SW land and 8 families were found in LC land. The number of individuals on SW land was 6,351 and on LC land was 2,297. The Apidae, Formicidae, Ichneumonidae, Platygastridae, Sphecidae, and Vespidae families are found in almost all fields. The total abundance index of the Hymenoptera order family in SW land (73.438%) was higher than the index of the total abundance of the Hymenoptera order family in the LC land (26.561%). The highest family abundance index was Formicidae, namely 65.101%, followed by the Vespidae family (26.237%) and the Apidae family (5.087%). The diversity index of the Hymenoptera order in the LC land had a higher value (2.741) than the diversity index in the SW field (2.165). The conclusion is that the composition of the insect family of the Hymenoptera order in LC land was higher than in SW land, but the number of individual insects in SW land was higher than in LC land. The abundance index of the Hymenoptera order in SW land was higher than that in LC land. The insect diversity index of the Hymenoptera order in LC land was higher than in SW land. It is recommended to research the role of various insect species from the Hymenoptera order in the SW land and LC land of theÃÂ  Palembang city.